The influence of particular entrance exam score on enrolment and graduation at the University of Criminal Investigation and Police Studies - Janković Radivoje; Kukić Filip; Koropanovski Nenad (NBP: Nauka, bezbednost, policija)
The aim of the research was to determine if there was a difference in the entrance exam scores between the candidates who enrolled and those who did not at the University of Criminal Investigation and Police Studies (UCIPS), as well as between the graduates and non-graduates. Analysing the data from 1657 candidates who participated in the UCIPS entrance exam, the study categorizes candidates based on gender, entrance exam results, and graduation. The research focuses on High School Success (HSS), and three components of the entrance exam: Serbian Language Test (SLT), General Knowledge Test (GKT), and Basic Physical Abilities (BPA). To examine the impact of all variables, the study applied an independent t-test to compare group differences, followed by effect size calculations. The findings reveal that candidates who enrolled, regardless of gender, exhibited significantly higher scores and larger effect sizes in all exam segments compared to those who did not enrol. Additionally, graduates exhibited higher performance in HSS, SLT, and GKT, which may indicate the predictive value of these components for academic success. Conversely, no significant difference was found in BPA scores between graduates and non-graduates, underscoring its unique eliminatory role in the selection process, as BPA is the only test with an eliminatory threshold. The study also emphasizes the role of continuous learning, perseverance, and motivation, as reflected in higher entrance exam scores, in influencing academic achievement. The research suggests that implementing a minimum score threshold for various exam components could potentially enhance learning efficiency and graduation rates at the UCIPS.